2021
DOI: 10.21037/hbsn-20-263
|View full text |Cite
|
Sign up to set email alerts
|

The presence of NAFLD in nonobese subjects increased the risk of metabolic abnormalities than obese subjects without NAFLD: a population-based cross-sectional study

Abstract: Background: With lifestyle modification and over-nutrition, the prevalence of nonalcoholic fatty liver disease (NAFLD) has been increasing annually. Here we aimed to assess the updated prevalence of NAFLD, and to evaluate the association of NAFLD with metabolic abnormalities according to gender, body mass index and age.Methods: A population-based cross-sectional study was conducted in Shanghai from December 2016 to July 2017. With a three-stage stratified sampling strategy, 3,717 eligible participants were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…And a meta-analysis ( 5 ) which involved 26,196 participants carried out by Renehan et al also descripted that elevated body mass index (BMI) was significantly associated with ETE and multifocality in overweight and obese patients and only obesity was significantly associated with increased tumor size. The same effect can also be seen in many studies ( 6 , 7 ). Therefore, the aggressiveness of PTC may associated with the increase of BMI, so it is necessary to divide overweight and obese patients in different groups.…”
supporting
confidence: 83%
“…And a meta-analysis ( 5 ) which involved 26,196 participants carried out by Renehan et al also descripted that elevated body mass index (BMI) was significantly associated with ETE and multifocality in overweight and obese patients and only obesity was significantly associated with increased tumor size. The same effect can also be seen in many studies ( 6 , 7 ). Therefore, the aggressiveness of PTC may associated with the increase of BMI, so it is necessary to divide overweight and obese patients in different groups.…”
supporting
confidence: 83%
“…1 , the Kaplan–Meier curves showed the higher cumulative incidence of MS in lean NAFLD population than that in obesity/overweight non-NAFLD subjects. In a recent, Hu et al’s cross-sectional study also found that lean NAFLD present higher MS risk than overweight/obese non-NAFLD 24 . Two possible reasons may account for this phenomenon.…”
Section: Discussionmentioning
confidence: 91%
“…Two possible reasons may account for this phenomenon. One reason is that lean NAFLD is more likely a specific metabolic disease that is stronger correlated with MS than obesity 24 . Another one is the limitation of BMI in reflection of abdominal fat.…”
Section: Discussionmentioning
confidence: 99%
“…3 Longer duration and severity of NAFLD has been associated with increased risk of metabolic abnormalities. 4 However, the detailed degree of NAFLD was not reported in this study. Moreover, a recent study showed that increase in visceral adiposity was associated with a higher risk for CRA, indicating there might also be changes in the severity of NAFLD.…”
mentioning
confidence: 73%